). Work-family interface and well-being: The mediating role of personal energetic resources - Tavares, S. M. (17th European Congress of Work and Organizational Psychology: “Respectful and effective leadership: managing people and organizations in turbulent times”, 2015)
Purpose This research aimed to analyze the impact of work-family interactions on employees’ well-being, exploring the mediating role of the energetic resources in this relation. The Conservation of Resources Theory was used as a theoretical frame. Design/Methodology Study 1 (N= 143) investigated the link between work-family conflict (WFC), fatigue and employees’ report of chest pains using multisource data. Study 2 (N= 106) examined the effect of work-family enrichment (WFE) in employees’ life satisfaction through the enhancement of vigor. Data were collected with questionnaires Results Results from Study 1 showed that WFC is positively associated with the level of fatigue and the frequency of self-reported chest pains. Additionally, fatigue felt by the individual mediates the relationship between WFC and chest pains. Results from Study 2 evidenced that WFE is positively related to vigor and to employees’ life satisfaction. Moreover, WFE-life satisfaction relationship is mediated by the level of vigor reported by the employee. Limitations The cross-sectional and correlational nature of the actual data limits causal and temporal inferences Research/Practical Implications These findings suggest that the way work influences employee’s family roles is associated with the depletion and absorption of energetic resources. In turn, the energetic resources lost, or gained, have impact on individual’s well-being. Thus, managers should focus on creating opportunities for workers to better manage the work-family interface and, in parallel, encourage practices that allow individuals to restore their energy resources. Originality/Value One important contribution is the empirical test of one mechanism through which work-family intersection can have impact on employees’ well-being: the personal energetic resources.